Penilaian kesehatan ekosistem terumbu karang dan padang lamun di Tiaro (LMMA), Guadalcanal Barat, Kepulauan Solomon - Belade, Jimmy; Kodiran, Taryono; Wardiatno, Yusli (Badan Kerjasama Pusat Studi Lingkungan (BKPSL) se-Indonesia bekerjasama dengan Pusat Penelitian Lingkungan Hidup IPB (PPLH-IPB), 2025)
Coral reefs, seagrass meadows and associated fish communities are essential coastal ecosystems that provide significant ecological and economic benefits. However, these habitats are increasingly threatened by anthropogenic activities and climate change. This study assessed coral cover, reef fish composition and abundance and seagrass distribution in the Tiaro Locally Managed Marine Area (LMMA), Solomon Islands, to evaluate ecosystem health and conservation effectiveness. Ecological surveys at eleven sites revealed variable coral cover, ranging from 26% to 52%, with bleaching and disease most prevalent at Kotatave (11%) and Kokomu (10%). Herbivorous fish, particularly Pomacentridae and Acanthuridae, dominated the fish assemblages, while predatory species were scarce, suggesting trophic imbalance. Seagrass coverage varied across sites, with Cymodocea rotundata being the most dominant species, especially at Leleona (72% coverage). The findings highlight the interdependence of coral, seagrass and fish communities and emphasize the need for integrated, community-based conservation strategies to enhance ecosystem resilience.